The Printing Revolution in Early Modern Europe - Eisenstein Elisabeth L (Cambridge University Press, 1983)
This book is designed to give a stimulating survey of the communications revolution of the fifteenth century. Preface. The Emergence of Print Culture in the West, Interaction with Other Developments, Index.